The Role Of Women In Meaningful Participation In The General Election Supervisory Body Of Cianjur Regency - Maulidya, Azkia Ananda; Daming, Saharuddin; Fajri, Ibrahim (JURNAL MAHASISWA YUSTISI, 2025)
This study aims to analyze related to women's participation in general election supervision within the scope of the Cianjur Regency General Election Supervisory Body, in this study it is described related to the conditions of women's participation in general election supervision and examines the implementation of Article 92 paragraph (11) of Law No. 7 of 2017 concerning General Elections. This study uses a normative legal method, by reviewing the reality of the implementation of women's representation quotas in organizing general election supervision within the scope of the Cianjur Regency General Election Supervisory Body. The results of this study are that Cianjur Regency has still not been able to meet the quota of women's representation of 30% within the scope of the Cianjur Regency General Election Supervisory Body, however Bawaslu has carried out various improvement efforts ranging from education and training related to general elections, organizing socialization and counseling, and trying to eliminate community stereotypes about gender through the Participatory Supervisory Cadre School